2005
DOI: 10.1097/01.mlg.0000161346.30752.18
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Biofilms in Surgical Specimens of Patients with Chronic Rhinosinusitis

Abstract: Biofilms were demonstrated to be present in patients undergoing surgery for CRS; none of the patients without CRS had any evidence of biofilms. Although SEM is capable of demonstrating the biofilms' three-dimensional structure, glycocalyx, and water channels, it cannot clearly demonstrate the presence of bacteria within the biofilm. We were able to demonstrate evidence of bacteria in the biofilms on the subjects tested using TEM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
193
0
19

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 219 publications
(216 citation statements)
references
References 20 publications
4
193
0
19
Order By: Relevance
“…Ferguson reported a biofilm detection rate of 50 % by TEM [23]. SEM can detect the 3-D structure, glycocalyx, and water channels of biofilms, while TEM can detect evidence of bacteria [24]. In contrast to electron microscopy, Confocal Scanning Laser Microscope (CSLM) better preserves the structure of a biofilm.…”
Section: Discussionmentioning
confidence: 99%
“…Ferguson reported a biofilm detection rate of 50 % by TEM [23]. SEM can detect the 3-D structure, glycocalyx, and water channels of biofilms, while TEM can detect evidence of bacteria [24]. In contrast to electron microscopy, Confocal Scanning Laser Microscope (CSLM) better preserves the structure of a biofilm.…”
Section: Discussionmentioning
confidence: 99%
“…Pneumococcal biofilms have been detected on nasal septum biopsy specimens from humans with sinusitis, on septal epithelia of experimentally challenged mice, and form in vitro on cultured respiratory epithelial cells and abiotic surfaces covered with bacterial media (13)(14)(15)(16)(17). Biofilm formation during colonization is thought to confer protection against host defenses and desiccation (18,19).…”
mentioning
confidence: 99%
“…Further studies found significant differences in the rate of biofilms formation between control, CRS and refractory sinusitis (Bendouah et al, 2006;Psaltis et al, 2007;Sanclement et al, 2005).…”
Section: Biofilm and Rcrsmentioning
confidence: 89%
“…During this phase water channels are formed. Once biofilms reach maturity, bacteria slough off and embolize to other areaswhere the process may begin again (Sanclement et al,2005).…”
Section: Biofilm and Rcrsmentioning
confidence: 99%